Research Report : Cases of Good Practice to Overcome the Conflict in the Department of Valle del Cauca (2009)
This research report consists of a brief review of the results of the evaluation of five cases of good practice in the Department of Valle del Cauca, implemented by the Interdisciplinary Research Center (CIES) of the Faculty of Law and Social Sciences at Icesi University. The study was part of a bigger project sponsored by the Good Practice Bank (a database) of the United Nations Development Program (UNDP) in Colombia in 2008.